Potentiometric determination of phosphorus in biodiesel using chemically modified electrode with cobalt film - Sartori, Mayara C. [UNESP]; Zezza, Tina R. C. [UNESP]; Paim, Leonardo L. [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2014)
A cobalt film modified glassy carbon electrode was prepared by electrochemical deposition and its application was studied by potentiometry. The film modified electrode is used for the determination of phosphorus and exhibits a detection limit of 8.7 x 10 (5) mol L (1) with recovery of 96.9%. This method has been used for determination of phosphorus ions in biodiesel samples with satisfactory results. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; Phosphorus determination; Cobalt film; Glassy carbon modified